2017
DOI: 10.1002/2016gl071316
|View full text |Cite
|
Sign up to set email alerts
|

Local atmospheric forcing driving an unexpected California Current System response during the 2015–2016 El Niño

Abstract: The 2015–2016 El Niño contributed to large anomalies across the California Current System (CalCS), but these anomalies ceased unexpectedly in late 2015. Here we use a suite of three hindcast simulations with the Regional Oceanic Modeling System to assess the responsible mechanisms for this development. We find that the early buildup was primarily driven by the early onset of this event in the tropical Pacific, driving anomalies in the CalCS through the propagation of coastally trapped waves. In contrast, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 32 publications
4
52
0
3
Order By: Relevance
“…Qualitatively speaking, the peak CCS warming in winter 2015 and winter 2016 resemble our composite winter CCS warm events without El Niño for their lack of amplified nearshore SST warm anomalies maximized along the West Coast, features of the 2015-2016 warming also noted by Jacox et al [2016]. The 2015-2016 CCS warm period was also notable for having anomalously strong upwelling winds in the southern/central CCS, which is opposite to the typical pattern during El Niño periods [Jacox et al, 2016;Frischknecht et al, 2017]. Surprisingly, the CCS warming pattern from late summer 2014 into 2015, a period with tropical warming that failed to reach NOAA's criteria for declaring an El Niño event, showed more of the coastally amplified CCS warming featured in our Journal of Geophysical Research: Oceans 10.1002/2017JC013094 composites for events co-occurring with El Niño.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Qualitatively speaking, the peak CCS warming in winter 2015 and winter 2016 resemble our composite winter CCS warm events without El Niño for their lack of amplified nearshore SST warm anomalies maximized along the West Coast, features of the 2015-2016 warming also noted by Jacox et al [2016]. The 2015-2016 CCS warm period was also notable for having anomalously strong upwelling winds in the southern/central CCS, which is opposite to the typical pattern during El Niño periods [Jacox et al, 2016;Frischknecht et al, 2017]. Surprisingly, the CCS warming pattern from late summer 2014 into 2015, a period with tropical warming that failed to reach NOAA's criteria for declaring an El Niño event, showed more of the coastally amplified CCS warming featured in our Journal of Geophysical Research: Oceans 10.1002/2017JC013094 composites for events co-occurring with El Niño.…”
Section: Discussionsupporting
confidence: 52%
“…[]. The 2015–2016 CCS warm period was also notable for having anomalously strong upwelling winds in the southern/central CCS, which is opposite to the typical pattern during El Niño periods [ Jacox et al ., ; Frischknecht et al ., ]. Surprisingly, the CCS warming pattern from late summer 2014 into 2015, a period with tropical warming that failed to reach NOAA's criteria for declaring an El Niño event, showed more of the coastally amplified CCS warming featured in our composites for events co‐occurring with El Niño.…”
Section: Discussionmentioning
confidence: 99%
“…Each ENSO event evolves differently (e.g., Capotondi et al, 2015) and the variability between events, including the timing, strength, and location of temperature anomalies, can influence atmospheric teleconnections over the North Pacific (e.g., Calvo et al, 2017) and the propagation of coastally trapped waves (e.g., Frischknecht et al, 2015Frischknecht et al, , 2017. Atmospheric teleconnections, and the associated winds and air temperatures over the CalCS, are influenced by SSTs in other basins, including the Indian Ocean (e.g., Annamalai et al, 2007;Han et al, 2013) and the Kuroshio-Oyashio extension in the western North Pacific (e.g., Smirnov et al, 2015) and potentially by Arctic seaice concentrations (e.g., Alexander et al, 2004;Screen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A handful of observational studies have investigated the impact of the 1982/1983 El Niño on the physical regime of the CalCS (e.g., Simpson, 1983;Huyer and Smith, 1985) and the effect of the 2002/2003 El Niño on the physics and biology (e.g., Murphree et al, 2003;Schwing et al, 2002a). Several regional modeling studies have shown the connection between ENSO and the vertical transport, water column density, origins, and properties of upwelled water (Jacox et al, 2014(Jacox et al, , 2015b, and demonstrated the relative importance of remote versus local forcing on both the physics and the biogeochemistry of the CalCS (Frischknecht et al, 2015;Jacox et al, 2015a;Frischknecht et al, 2017). During the 2010/2011 La Niña, Nam et al (2011) observed decreases in O 2 and pH in the upwelling region along the coast that were 2-3 times larger than expected solely due to the cross-shore shoaling of the isopycnal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, we sum up the individual phytoplankton types to represent the total phytoplankton biomass. The model version used here is essentially the same as the one employed by Frischknecht et al (2017) but was extended to explicitly account for the sinking of particulate matter. Numerically, this is facilitated using a piecewise parabolic method (Carpenter et al, 1990;Colella & Woodward, 1984) to compute the associated mass fluxes of particulate organic carbon and ballasting minerals (Armstrong et al, 2002).…”
Section: Coupled Regional Oceanic Modeling System (Roms-bec)mentioning
confidence: 99%